PENGARUH KELENGKAPAN PENGISIAN MEDICAL DISCHARGE SUMMARY PASIEN RAWAT INAP TERHADAP IMPLEMENTASI SNARS EDISI 1 ELEMEN PENILAIAN MIRM 15 DI RUMAH SAKIT AMC CILEUNYI - Dina Sonia; Ayulia Maulinabila (Akademi Perekam dan Informasi Kesehatan Imelda, 2020)
This research aims to determine the effect of fillings completeness of inpatient medical discharge summary on implementation SNARS 1st edition MIRM 15 valuation element at Rumah Sakit AMC Cileunyi.The research method used quantitative method with descriptive approach, The data collecting that by distributing quessioneir, observation, interview and compeleted with literature study which has a close relevance to the problem. The sampling technique used is sampling technique saturated.From the research of this research, the problem that arise among others: 1) The high number of incomplete replenishment of inpatien medical discharge summary. 2) The absence of standard procedure operational (SPO) for discharge summary, and 3) Unfulfilled SNARS accreditation standard 1st edition MIRM 15 valuation element related discharge summary The advice given to fix the problem is 1) Make a review team every room that aims to coordinate and control the incomplete doctor registers. It is expected that the doctor may improve the completeness of the filling of medical records. 2) Socializing the new design in accordance with the provisions of the SNARS edition 1 MIRM 15 valuation element and reinforcing the filling instructions by making the SPO filling discharge summary.